Respon Eksplan Biji Gaharu (Aquilaria malaccensis Lamk.) Terhadap Pemberian 2,4-D Secara In Vitro (Effect of Plant Growth Regulator 2,4-D on Seed Explant A. malaccensis in vitro ) - Itonamy Boru Tonga; Edy Batara Mulya Siregar; Nelly Anna (Peronema Forestry Science Journal, 2013)
ITONAMY BORU TONGA. Effect of Plant Growth Regulator 2,4-D on  Seed Explant A. malaccensis in vitro. Guided by Dr. Ir.Edy Batara Muyla Siregar Ms. And Nelly Anna S. Hut. Msi. Aquilaria malaccensis Lamk. is one of the tree forest that are continuosly exploited. Currently, the Indonesian export of the agarwood was decreasing because its population was endangered by excessive logging. Agarwood propagation need technology for reproduction of agarwood multiplication. Research was undertaken to determine effect of plant growth regulator 2,4-D on seed explant A. malaccensisi in vitro has been performed. This research had purpose to determine  response of seed explant of gaharu by giving different cosentration 2,4-D and to measure growth and developtment result of seed explant of gaharu. This research used a complete Randomized Non Factorial Design with using MS as basic media by added 2 ppm of BAP. The treatment consisted of 2,4-D 2 ppm, 4 ppm, 6 ppm and 8 ppm. Observation made explants fourty two days after planting. The parameter observed were the emergence of callus, callus color and  texture of the callus.  The result showed that callus was obtained as response of A. malaccensis seed explant with 2,4 D and BAP. The concentration 2,4-D 2 ppm showed the best result for the emergence of callus. Callus color is dominate by white and a bit yellow or scoring 4, and the callus texture is dominate by compact callus and compact with node. Keywords: Effect, 2,4- D, in vitro, A. malaccensis Lamk.